Crystalline arrays of molecular rotors with TIPS-trityl and phenolic-trityl stators using phenylene, 1, 2-difluorophenylene and pyridine rotators1. Issue 68 (25th July 2015) - Arcos-Ramos, Rafael; Rodriguez-Molina, Braulio; Gonzalez-Rodriguez, E.; Ramirez-Montes, Pedro I.; Ochoa, Maria Eugenia; Santillan, Rosa; Farfán, Norberto; Garcia-Garibay, Miguel A.
<x xml:space="preserve">Abstract</x> Molecular rotors based on substituted-trityl stators provide crystalline arrays capable of supporting different rotators through non-covalent interactions.